2007
DOI: 10.1210/en.2007-0820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transgenic Overexpression of SH2-Containing Inositol 5′-Phosphatase 2 on Glucose Metabolism and Insulin Signaling in Mice

Abstract: SH2-containing inositol 5'-phosphatase 2 (SHIP2) is a 5'-lipid phosphatase hydrolyzing the phosphatidylinositol (PI) 3-kinase product PI(3,4,5)P(3) to PI(3,4)P(2) in the regulation of insulin signaling, and is shown to be increased in peripheral tissues of diabetic C57BL/KSJ-db/db mice. To clarify the impact of SHIP2 in the pathogenesis of insulin resistance with type 2 diabetes, we generated transgenic mice overexpressing SHIP2. The body weight of transgenic mice increased by 5.0% (P < 0.05) compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 44 publications
(56 reference statements)
0
53
0
1
Order By: Relevance
“…Therefore, it is likely that SHIP2, Filamin A, and LL5␤ help a cell to move in one direction smoothly. Moreover, the ability of PtdIns(3,4,5)P 3 and SHIP2 to regulate various cellular responses, such as the insulin response (27), and the reciprocal regulation of PtdIns(3,4,5)P 3 with Filamin A-LL5␤ reported here suggest that these findings are significant for the general understanding of such events, and possibly, for the understanding of related diseases.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, it is likely that SHIP2, Filamin A, and LL5␤ help a cell to move in one direction smoothly. Moreover, the ability of PtdIns(3,4,5)P 3 and SHIP2 to regulate various cellular responses, such as the insulin response (27), and the reciprocal regulation of PtdIns(3,4,5)P 3 with Filamin A-LL5␤ reported here suggest that these findings are significant for the general understanding of such events, and possibly, for the understanding of related diseases.…”
Section: Discussionmentioning
confidence: 59%
“…PI(3,4,5)P 3 accumulation promotes the activity of signaling molecules, such as Akt; by reducing PI(3,4,5)P 3 accumulation, SHIP2 acts as a negative regulator of insulin-induced Akt signaling (7). Indeed, transgenic mice overexpressing SHIP2 have reduced glucose tolerance and blunted Akt activation in classic insulin target tissues (8).…”
Section: D/+mentioning
confidence: 99%
“…Lipid phosphatase SHIP2 downregulates PI3K mediated signalling, induced by insulin and other growth factors, by hydrolyzing PI(3,4,5,)P 3 to PI(3,4)P 2 (Blero et al 2001. SHIP2 overexpression in mice has a negative effect on glucose tolerance (Kagawa et al 2008,Fukui et al 2005 and SHIP2 knockout mice appear resistant to high fat diet-induced obesity and insulin resistance (Sleeman et al 2005), and in addition, inhibition of SHIP2 in the liver has been shown to improve glucose tolerance in diabetic mice (Grempler et al 2007). Taken together, SHIP2 is a downregulator of PI3K mediated insulin signalling, that is known to function in liver, muscle and adipose cells, but its role in the kidney has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%